Licenciatura em Educação do Campo: propostas em disputa na perspectiva de estudantes do curso de Matemática da UFMG - Josinalva Rodrigues Sá (2016)
This work aims to identify and analyze ways in which the students of the Rural Education Mathematics Qualification Program at UFMG understand the curriculum proposal of this course, in relation to training in mathematics and mathematics teaching practices in Rural Education. In particular, he sought to reflect on how students mobilize disputing discourses, when they take positions in relation to curriculum proposal discourses which establish the, and constitute themselves in, pedagogical practices of training Math Teachers of Rural Education. The empirical material submitted for analysis consists on narratives and transcripts of interactions between students and teachers-trainers occurred in class disciplines working math content for the 5th Time School of this course, in which we identified echoes of discourses about curriculum. We operationalized our analysis using: studies on the proposal of Rural Education and the training of teachers to work in its context; reflections on curriculum; perspectives of mathematics education that emphasize the political dimension of teaching practices; and the idea of appropriation of numeracy practices as appropriation of speeches. The classroom situations analyzed allowed us to see, in the ways in which subjects appropriate school numeracy practices: discourses on curriculum as significance practices of the principles of Rural Education and Mathematics Education, inspired by Freirian conceptions; discourses on curriculum as power relations, when students posed themselves against the maintenance of certain traditional practices in mathematics education; and discourses on curriculum as a practice that produces social identity. This study contributes to the reflections and the training practices of educators focused to work in the rural schools, and also to parameterize curricular proposals for rural degrees.